2013
DOI: 10.1371/journal.pone.0075221
|View full text |Cite
|
Sign up to set email alerts
|

Overtreatment of COPD with Inhaled Corticosteroids - Implications for Safety and Costs: Cross-Sectional Observational Study

Abstract: IntroductionCombined inhaled long-acting beta-agonists and corticosteroids (LABA+ICS) are costly. They are recommended in severe or very severe chronic obstructive pulmonary disease (COPD). They should not be prescribed in mild or moderate disease. In COPD ICS are associated with side-effects including risk of pneumonia. We quantified appropriateness of prescribing and examined the risks and costs associated with overuse. MethodsData were extracted from the electronic and paper records of 41 London general pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
114
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(131 citation statements)
references
References 23 publications
10
114
1
6
Order By: Relevance
“…In a study that analyzed data extracted from records of London general practices, the investigators reported a 25% incidence of overtreatment with ICS when compared with the 2011 revised GOLD guidelines' recommendations [White et al 2013]. According to another observational study from Italy, ICS were over-prescribed in up to 62% of the subjects [Corrado and Rossi, 2012].…”
Section: Risk/benefit Ratio and Indicationsmentioning
confidence: 99%
“…In a study that analyzed data extracted from records of London general practices, the investigators reported a 25% incidence of overtreatment with ICS when compared with the 2011 revised GOLD guidelines' recommendations [White et al 2013]. According to another observational study from Italy, ICS were over-prescribed in up to 62% of the subjects [Corrado and Rossi, 2012].…”
Section: Risk/benefit Ratio and Indicationsmentioning
confidence: 99%
“…Overprescription of inhaled steroids was associated with adverse events such as pneumonia, and higher costs. 6 In COPD, where treatment is often escalated in the hope of easing the burden of disease, clinicians should confirm the diagnosis before treatment, and then consider both the risks and benefits of treatment, and the costs where the benefits are unproven. Recently, Carter et al 7 proposed a theoretical, generic terminology to clearly differentiate within clinical situations regarding inadequate diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…This observation seems to support a recent study indicating a tendency toward overtreatment with inhaled corticosteroids in mild COPD. 32 Lastly, as a minor limitation, the GOLD A-D grading was not officially implemented in clinical practice until 2011. 10 Nevertheless, our analyses clearly show that the GOLD A-D grading was already an important driver of treatment in COPD in the general population even before the official implementation.…”
mentioning
confidence: 99%